Acute lung injury after plasma exchange in a patient with anti-MDA5 antibody-positive, rapidly progressive, interstitial lung disease：A case report. (2020) - Kagawa, Hiroyuki; Tsujino, Kazuyuki; Yamamoto, Yuji; Iwai, Ami; Hara, Reina; Matsuki, Takanori; Fukushima, Kiyoharu; Oshitani, Yohei; Yoshimura, Kenji; Miki, Mari; Miki, Keisuke; Kitada, Seigo; et al.
Abstract: The presence of anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5 Ab) is closely associated with rapidly progressive interstitial lung disease (RP-ILD) in patients with clinically amyopathic dermatomyositis. Despite intensive immunosuppressive therapies, some of these patients still have a poor prognosis with few treatment options. Although removal of pathogenic autoantibodies and cytokines by plasma exchange (PE) could be a treatment option, its safety and efficacy have never been determined. We report a patient with anti-MDA5 Ab-positive RP-ILD who was refractory to intensive therapies including steroids, cyclosporine, and intravenous cyclophosphamide, and then treated by PE to prevent the progression of RP-ILD. Shortly after the initiation of PE therapy, however, his respiratory condition suddenly deteriorated due to acute pulmonary edema and the patient died on the following day. Transfusion-related acute lung injury (TRALI) would be the most likely cause of the acute pulmonary edema because there was no sign of circulatory overload. To the best of our knowledge, this is the first report showing a critical adverse event associated with PE therapy for these patients. This case supports the idea that the presence of ILD could increase a risk for TRALI and therefore we should carefully evaluate the eligibility for PE therapy of anti-MDA5 Ab-positive RP-ILD patients given the risk of acute lung injury. Further studies collecting more clinical data are necessary to assess the efficacy, safety, and risk factors of PE therapy for these patients.